2007
DOI: 10.1093/eurpub/ckl119
|View full text |Cite
|
Sign up to set email alerts
|

Are manual workers at higher risk of death than non-manual employees when living in Swedish municipalities with higher income inequality?

Abstract: The findings suggest that there could be a differential impact from income inequality on risk of death, dependent on individuals' social position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…An analysis of Swedish individuals aged 40–64 years evaluating occupation as a modifier found that income inequality was associated with a higher risk of mortality for unskilled manual workers only 15. A US study examining individual income and ethnicity as modifiers found effects on mortality were largest in poor white people 9.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of Swedish individuals aged 40–64 years evaluating occupation as a modifier found that income inequality was associated with a higher risk of mortality for unskilled manual workers only 15. A US study examining individual income and ethnicity as modifiers found effects on mortality were largest in poor white people 9.…”
Section: Discussionmentioning
confidence: 99%
“…There is earlier evidence from other Nordic countries that is in accordance with this hypothesis. Dahl et al (2006) have reported that the effects of economic inequality on mortality are particularly marked among socio‐economically disadvantaged groups in Norway, 13 and the findings by Henriksson et al (2007), through the use of the Swedish census, point out that there could be a differential impact from income inequality on mortality, dependent on individuals’ social position. Overall, our results do not change much when we estimate the models separately for those individuals who have at most 10 years of education.…”
Section: Resultsmentioning
confidence: 99%
“…analyses included 2,916,576 individuals in 38 studies considering SRH and 14 studies with 10,727,470 million individuals considering mortality 141,[167][168][169][170][171][172][173][174][175][176][177][178][179] (study characteristics in Appendices 15 and 16, respectively). An additional seven reports considering SRH [180][181][182][183][184][185][186] and eight considering mortality, [187][188][189][190][191][192][193][194] including one natural experimental study, 191 were included in one or more of the subgroup or sensitivity analyses.…”
Section: Evidence Against Bh Viewpointmentioning
confidence: 99%
“…191 Despite its favorable study design, estimates from the natural experimental study were excluded from the main analysis, as it used a subset of the Swedish census that overlaps, but is smaller than, another report included in the primary meta-analysis. 171 Of the studies considering SRH, most used the Gini coefficient to measure income inequality except for two that used the Theil index 129,130 and one that used median share. 141 All but six (15.8%) were cross-sectional.…”
Section: Evidence Against Bh Viewpointmentioning
confidence: 99%